Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/ijerph20186730
|View full text |Cite
|
Sign up to set email alerts
|

School-Level Socioeconomic Status and Nutrient Content of Outdoor Food/Beverage Advertisements

Phoebe R. Ruggles,
Jacob E. Thomas,
Natalie S. Poulos
et al.

Abstract: We examined if areas around schools with more students of lower socioeconomic status (SES) have more total food/beverage advertisements and/or more advertisements with poorer nutritional content as compared to areas around schools with fewer students with lower SES. All outdoor food/beverage advertisements within a half-mile radius of 47 middle and high schools in the United States were objectively documented in 2012 and coded for nutritional content. The total number of advertisements and the macronutrient an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Research consistently shows disparities in unhealthy food and beverage advertising exposure by SES [ 32 ]. Previous research has found that neighborhood-level income demographics are also associated with the outdoor food and beverage advertising environment, with lower-income areas consistently having higher densities of food and beverage marketing than higher-income areas [ 33 37 ]. However, few have specifically examined if this economic disparity in advertising applies to school environments [ 37 ], nor if the types of beverages advertised vary by neighborhood income level.…”
Section: Introductionmentioning
confidence: 99%
“…Research consistently shows disparities in unhealthy food and beverage advertising exposure by SES [ 32 ]. Previous research has found that neighborhood-level income demographics are also associated with the outdoor food and beverage advertising environment, with lower-income areas consistently having higher densities of food and beverage marketing than higher-income areas [ 33 37 ]. However, few have specifically examined if this economic disparity in advertising applies to school environments [ 37 ], nor if the types of beverages advertised vary by neighborhood income level.…”
Section: Introductionmentioning
confidence: 99%